Efficacy and safety of rituximab in the treatment of membranous nephropathy: A systematic review and meta-analysis. Issue 16 (April 2020) - Lu, WanJun; Gong, ShuHao; Li, Juan; Luo, HongWen; Wang, Ying
Abstract: Background and objectives: Rituximab (RTX) is considered to be a promising drug for curing membranous nephropathy. However, the efficacy and safety of RTX in treating membranous nephropathy remain uncertain. This meta-analysis aimed to investigate the efficacy and safety of RTX in patients with membranous nephropathy. Methods: A literature search was performed using Pubmed, Embase, OVID, and Cochrane Library and randomized controlled trials (RCTs) case-controls and cohort studies published till 30 July 2019 were assessed. The studies assessing the efficacy and safety of RTX in patients with membranous nephropathy were included. Results: Eight relevant trials involving 542 patients were included in the meta-analysis. It was found that RTX did not significantly improve serum albumin levels and e-GFR when compared with the control group (including cyclosporine and cyclophosphamide, chlorambucil, prednisone, non-immunosuppressive anti-proteinuria treatment), serum albumin levels (OR = 0.31, 95%CI–0.12–0.74, P  = .15), e-GFR (OR = –1.49, 95%CI–17.14–14.17, P  = .85). However, RTX did reduce the serum creatinine (OR = –0.01, 95%CI–0.36–0.34, P  = .95) and urinary protein (OR = –2.39, 95%CI –7.30 –2.53, P  = .34) levels. Also, in comparison to the control group, RTX did improve the total remission rate (OR = 1.63, 95%CI 0.48–5.54, P  = .43), achieve a higher rate of complete remission (OR = 2.54, 95%CI 1.65–3.90, P  < .01) and also reduced the amount of M-type phospholipase A2 receptor-Antibody depletion in patients (OR = 5.59, 95%CI 1.81–17.2, P  = .003). RTX-related adverse events were mostly mild (most infusion-related reactions) in nature and serious adverse events were rare. Conclusion: RTX proved to be efficient, well-tolerated and a safe drug in the treatment of membranous nephropathy. Most patients reach complete remission during the follow-up period, and relapse is rare. RTX may turn out to be promising in membranous nephropathy patients.